Characteristics of HIV-positive pregnant women and HIV- and antiretroviral therapy-exposed fetuses: A case-control study - Tung-Che Hung; Li-Cheng Lu; Mei-Hui Lin; Yu-Chia Hu; Chien-Yu Cheng; Shu-Hsing Cheng; Chien-Yu Lee (Journal of Infection in Developing Countries)
Introduction: This study determined risk factors, obstetric comorbidities, and fetal conditions among HIV-positive mothers to improve their maternal care.